Integrating Cycled Enzymatic DNA Amplification and Surface-Enhanced Raman Scattering for Sensitive Detection of Circulating Tumor DNA - Miao, Xinxing; Fang, Qianqian; Xiao, Xiang; Liu, Sidi; Wu, Renfei; Yan, Jun; Nie, Baoqing; Liu, Jian (Frontiers in Molecular Biosciences, 2021)
Circulating tumor DNA (ctDNA) represents an emerging biomarker of liquid biopsies for the development of precision cancer diagnostics and therapeutics. However, it remains challenging to sensitively detect ctDNA, due to their short half-life and low concentrations in blood samples. Here we report a new method to address this challenge by integrating cycled enzymatic DNA amplification and Au nanoparticle@silicon-assisted surface-enhanced Raman scattering (SERS) techniques. We have demonstrated reproducible identification of a single-base mutated ctDNA sequence of diffuse intrinsic pontine gliomas (DIPG), with the limit of detection (LOD) as low as 9.1 fM. It promises a useful tool to analyze trace amounts of ctDNA for translational medicine including early diagnosis, therapeutic effect monitoring and prognosis of cancer patients.